Dysphoric variant formation of post-traumatic stress disorder in combs - Kateryna Mуhailіvna Semenenko (Kazimierz Wielki University, 2020)
Nowadays, more combatants are suffering from the effects of an extreme event in the war zone. Specific mental trauma leads to psychiatric disorders that have common characteristics, which allows them to be separated into a separate heading - F43.1 (PTSD-post-traumatic stress disorder) in MKH-10. It is revealed that more than 26.5% of fighters from 324 respondents who returned from the ATO zone have clear signs of dysphoric variant of PTSD, including flashbacks, emotional numbness, unmotivated vigilance, maladaptation, and psychosomatic disorders. It is important to determine the criteria for the distribution of this condition, which is essential for the treatment and resolution of social issues. The purpose of the work is to identify the etiological factors and characteristic manifestations of dysphoric variant of PTSD in combatants. Materials and methods: On the basis of the Vinnitsa Regional Clinical Hospital of War Veterans (VRCHWV), as well as on the basis of the expert department of the scientific research institute of rehabilitation of the of disabled people of Mykola Pirogov VNMU (SRIRDP) surveyed 86 respondents suffering from dysphoric variant of PTSD. Basic methods of research: clinical anamnestic, clinical psychopathological (clinical interview), socio-demographic (questionnaire), psychodiagnostic, statistical. The results showed a significant correlation between the personal differential indices and the assessment of the level of neuro-psychic stability according to Pearson and Spearman correlation coefficients (P <0.01). Almost all respondents showed high and medium levels of self-esteem (6.4 and 92.3% respectively). According to the results of the surveys, the arithmetic mean of the assessment of neuropsychiatric resistance (25.62 ± 11.62) indicates a tendency for neuropsychiatric breakdowns. Conclusions: The relevance of anxiety level research is related not only to its high prevalence in patients, but also with the tendency to chronicize the process and fix symptoms in the form of persistent personality changes. Timely identification of problems will improve the effectiveness of the respondents' medical work.